Water Deficits and Mineral Uptake in Rice - O'Toole, J.C.; Baldia, E.P. (Wiley, 1982)
Water deficits result in decreased gas exchange between plant leaves and the atmosphere. Decrease in transpiration from water stressed plant leaves is well known; however, the relationship of transpiration to uptake of N, P, and K during water stress is less well documented. Rice plants (Oryza sativa L.) were grown in containers and subjected to water stress. Soil and plant water potential, transpiration rate, leaf area, dry wieght, uptake of N, P and K and atmospheric evaporative demand were monitored over an 18 day drying period. Decreased transpiration rate was the most sensitive variable to water stress. Transpiration of the stress treatment differed significantly from control plants when soil water potential was in the range −0.02 to −0.15 MPa. Dawn leaf water potential, alternately used to estimate soil water potential, was between −0.06 and −0.25 MPa when transpiration and N, P and K uptake of stressed plants deviated from control plants. Although extrapolation of container experiments must be done with care, our results show transpiration and nutrient uptake to be highly correlated during the development of even mild soil and plant water stress. However, interpretation of results, even in this simple system, is complex. The linear and curvilinear relationships among elements of the soil‐plant‐atmosphere continuum are discussed as aides in interpretation of results.